(untitled) (Práxis Educativa, 2024)
There is an ever-renewed challenge of rethinking education and its training possibilities. Among the countless variables that involve these debates, it lies the ethical possibilities in a contemporary world that has individualism and productivism as the fundamental pillars for capturing the subjectivity of human beings. In view of the biopolitical devices that subject human beings to the anxieties of insecurity in the absolutization of the self, we wish to develop, in this text, reflections grounded in epistemological assumptions primarily supported by Giorgio Agamben, Humberto Maturana, Francisco Varela and Ximena Dávila Yáñez, who, despite being diverse in their approaches, they desecrate traditionalism arising from the logic of objectivity, massification, absolute truths, blind obedience, among others. Our objective aims to understand, as educational challenges, the invitations for different uses of the training potential to be reconstructed into highways of ethical co-responsibility, justice and freedom. This is a qualitative bibliographic study. We are human beings and, as such, not predetermined, which opens doors to choices, responsibilities and freedom, making formative dynamics possible for an ethical existence. Keywords: Education. Autopoiesis. Formative dynamics.